The effect of chronic kidney disease on the urine proteome in the domestic cat (Felis catus). Issue 1 (April 2015) - Ferlizza, E.; Campos, A.; Neagu, A.; Cuoghi, A.; Bellei, E.; Monari, E.; Dondi, F.; Almeida, A.M.; Isani, G.
Highlights: Chronic kidney disease is a major cause of mortality in cats, but sensitive and specific biomarkers are currently lacking. This study aimed to apply proteomic techniques to map the cat urine proteome and compare it with that in cats with CKD. Our work produced a reference map of the normal cat urine proteome containing 20 proteins identified by mass spectrometry. We identified 13 proteins differentially represented in CKD. Most of these proteins are indicative of tubulointerstitial damage when not reabsorbed or not secreted. Abstract: Chronic kidney disease (CKD) is a major cause of mortality in cats, but sensitive and specific biomarkers for early prediction and monitoring of CKD are currently lacking. The present study aimed to apply proteomic techniques to map the urine proteome of the healthy cat and compare it with the proteome of cats with CKD. Urine samples were collected by cystocentesis from 23 healthy young cats and 17 cats with CKD. One-dimensional sodium-dodecyl-sulfate polyacrylamide gel electrophoresis (1D-SDS-PAGE) was conducted on 4–12% gels. Two-dimensional electrophoresis (2DE) was applied to pooled urine samples from healthy cats ( n = 4) and cats with CKD ( n = 4), respectively. Sixteen protein bands and 36 spots were cut, trypsin-digested and identified by mass spectrometry. 1D-SDS-PAGE yielded an overall view of the protein profile and the separation of 32 ± 6 protein bands in the urine of healthy cats, while CKD cats showed significantly fewer bands ( P < 0.01). 2-DE was essential in fractionation of the complex urine proteome, producing a reference map that included 20 proteins. Cauxin was the most abundant protein in urine of healthy cats. Several protease inhibitors and transport proteins that derive from plasma were also identified, including alpha-2-macroglobulin, albumin, transferrin, haemopexin and haptoglobin. There was differential expression of 27 spots between healthy and CKD samples ( P < 0.05) and 13 proteins were unambiguously identified. In particular, increased expression of retinol-binding protein, cystatin M and apolipoprotein-H associated with decreased expression of uromodulin and cauxin confirmed tubular damage in CKD cats suggesting that these proteins are candidate biomarkers.